Dietary Fiber Is Essential to Maintain Intestinal Size, L-Cell Secretion, and Intestinal Integrity in Mice - Hunt, Jenna Elizabeth; Hartmann, Bolette; Schoonjans, Kristina; Holst, Jens Juul; Kissow, Hannelouise (Frontiers in Endocrinology, 2021)
Dietary fiber has been linked to improved gut health, yet the mechanisms behind this association remain poorly understood. One proposed mechanism is through its influence on the secretion of gut hormones, including glucagon-like peptide-1 (GLP-1) and glucagon-like peptide-2 (GLP-2). We aimed to: 1) investigate the impact of a fiber deficient diet on the intestinal morphological homeostasis; 2) evaluate L cell secretion; and 3) to ascertain the role of GLP-1, GLP-2 and Takeda G protein-receptor-5 (TGR5) signaling in the response using GLP-1 receptor, GLP-2 receptor and TGR5 knockout mice. Female C57BL/6JRj mice (n=8) either received a standard chow diet or were switched to a crude fiber-deficient diet for a short (21 days) and long (112 days) study period. Subsequent identical experiments were performed in GLP-1 receptor, GLP-2 receptor and TGR5 knockout mice. The removal of fiber from the diet for 21 days resulted in a decrease in small intestinal weight (p<0.01) and a corresponding decrease in intestinal crypt depth in the duodenum, jejunum and ileum (p<0.001, p<0.05 and p<0.01, respectively). Additionally, colon weight was decreased (p<0.01). These changes were associated with a decrease in extractable GLP-1, GLP-2 and PYY in the colon (p<0.05, p<0.01 and p<0.01). However, we could not show that the fiber-dependent size decrease was dependent on GLP-1 receptor, GLP-2 receptor or TGR5 signaling. Intestinal permeability was increased following the removal of fiber for 112 days. In conclusion, our study highlights the importance of dietary fiber to maintain intestinal weight, colonic L cell secretion and intestinal integrity.